Evaluation of the performance of tropical cyclone track prediction techniques - CHAN, JOHNNY C. L. (MAUSAM, 1997)
ABSTRACT. This paper reviews the methods by which techniques for predicting tropical cyclone (TC) motion can be evaluated. Different error measures (forecast error, systematic error, and cross-track and along-track errors) are described in detail. Examples are then given to show how these techniques can be further evaluated by stratifying the forecasts based on factors related to the TC, including latitude, longitude, intensity change, size and past movement. Application of the Empirical-Orthogonal-Function (EOF) approach to represent the environmental flow associated with the TCs is also proposed. The magnitudes of the EOF coefficients can then be used to stratify the forecasts since these coefficients represent different types of flow fields. A complete evaluation of a forecast technique then consists of a combination of analyzing the different error measures based on both the storm- related factors and the EOF coefficients.